Use of vasopressors in patients with acute kidney injury on continuous kidney replacement therapy. - Ambika Ramesh; Akshith Doddi; Aisha Abbasi; Mohammad A Al-Mamun; Ankit Sakhuja; Khaled Shawwa (PLoS ONE)
Objective To investigate whether the use of a specific vasopressor was associated with increased mortality or adverse outcomes in patients with acute kidney injury (AKI) receiving continuous kidney replacement therapy (CKRT). Methods Patients with AKI who underwent CKRT between 1/1/2012-1/1/2021 at a tertiary academic hospital were included. Cox proportional hazard model was used to assess the relationship between time-dependent vasopressor dose and in-hospital mortality. Results There were 641 patients with AKI that required CKRT. In-hospital mortality occurred in 318 (49.6%) patients. Those who died were older (63 vs 57 years), had higher SOFA score (10.6 vs 9) and lactate (6 vs 3.3 mmol/L). In multivariable model, increasing doses of norepinephrine [HR 4.4 (95% CI: 2.3-7, p<0.001)] per 0.02 mcg/min/kg and vasopressin [HR 2.6 (95% CI: 1.9-3.2, p = 0.01)] per 0.02 unit/min during CKRT were associated with in-hospital mortality. The model was adjusted for vasopressor doses and fluid balance, SOFA score, lactate and other markers of severity of illness. Baseline vasopressor doses were not associated with mortality. Most vasopressors were associated with positive daily fluid balance. Among survivors at day 30, mean values of vasopressors were not associated with persistent kidney dysfunction. Conclusion The associations between norepinephrine and vasopressin with in-hospital mortality could be related to their common use in this cohort.